Labor Productivity and Real Exchange Rate : The Balassa-Samuelson Disconnect in the former Yugoslav Republic of Macedonia - Loko, Boileau (IMF Working Papers; Working Paper ;, 2005)
This paper seeks to investigate the transmission mechanisms linking productivity to the real exchange rate in the former Yugoslav Republic of Macedonia. At first glance, the stylized facts-low labor productivity growth and a trend real depreciation-suggest that a Balassa- Samuelson effect is in play. We find that the relationship between the two is not a result of the traditional Balassa-Samuelson effect. Instead, the depreciation of the real exchange rate reflects mainly the behavior of prices in the tradable sector. We argue that the depreciating real exchange rate may reflect a prolonged transition associated with slow technological growth and the low quality of the country's tradable-goods basket.